Genetic Associations of IL-2 (rs2069762) and EGR3 (rs3750192) Polymorphisms with Schizophrenia: A Meta-Analysis - Anilkumar, Anu Shibi; Thomas, Sheena Mariam; Veerabathiran, Ramakrishnan (Folia Medica Indonesiana, 2024)
Highlights: 1.The novelty of this study lies in its thorough examination of gene polymorphisms and their associations with schizophrenia risk across different populations. 2.This meta-analysis provides new insights by highlighting the lack of reliable association for interleukin-2 (IL-2) rs2069762 and revealing a substantial protective effect of early growth response 3 (EGR3) rs3750192 in specific ethnic groups, particularly among Polish and Chinese. Abstract Although genome-wide association studies have identified numerous genes linked to schizophrenia, their specific roles remain unclear. This meta-analysis sought to explore the association of polymorphisms in the interleukin-2 (IL-2) rs2069762 and early growth response 3 (EGR3) rs3750192 with schizophrenia susceptibility. The literature review on schizophrenia was conducted using databases, such as PubMed, Embase, and Google Scholar, with specific search terms. The inclusion criteria focused on studies linking IL-2, EGR3, and schizophrenia, requiring genotypic and allele frequency data. The data extraction included genotypic and allelic frequencies, sample size, publication details, Hardy-Weinberg equilibrium values, and ethnicities. Fixed-effect and random-effect models were employed for analyses under allele, dominant, recessive, and overdominant models. Subgroup analyses were conducted by ethnicity. No significant associations with schizophrenia risk were found for IL-2 rs2069762 across all genetic models. The allele (OR=0.94, p=0.34), dominant (OR=0.85, p=0.55), recessive (OR=0.93, p=0.76), and overdominant (OR=0.94, p=0.76) models showed non-significant results. Conversely, EGR3 rs3750192 demonstrated a significant association in the dominant (OR=0.73, p=0.012) and homozygous (OR=0.70, p=0.004) models, suggesting a protective effect. The subgroup analyses indicated ethnic differences, with Polish and Chinese showing significant protective effects for IL-2 and EGR3, respectively. While IL-2 rs2069762 lacks a consistent association with schizophrenia, EGR3 rs3750192 may confer a protective effect, particularly in certain ethnic groups.